A Different Kind of Political Islam: The Ideas of The Sudanese Scholar Mahmoud Mohamed Taha - Cristi Rusin (Nur Science Institute, 2025)
Ustadh Mahmoud Mohamed Taha is one of the least known but most interesting figures in Sudanese history. The movement he led, the Republican Brotherhood, played a significant role in the debates within Sudanese society during the 1950s-1980s. This study presents the life and thought of this figure, analyzing his main work: The Second Message of Islam. This volume forms the foundation of his entire Islamist ideology, a progressive, pacifist, and tolerant Islamism very different from that of the Muslim Brotherhood in Egypt. The essential characteristic of his conception is linked to the distinction between the Islamic message revealed in Mecca and that in Medina — more precisely, between the Meccan and Medinan surahs. He believed that the core teachings of the Qur’an with universal and timeless applicability are the Meccan ones, whereas the laws from Medina are temporary. These unique interpretations by Taha brought him into direct conflict with the Sudanese authorities, who accused him of apostasy — a conflict that ultimately culminated in his execution. His movement and ideas, unusual for traditional Islam, remain a relevant example of an attempt to modernize Islam and perhaps could have contributed to preserving Sudan's unity. REFERENCES Adrahtas, Vassilios (2020),